1989
DOI: 10.1159/000167999
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Exercise for End-Stage Renal Disease Patients Immediately following High-Efficiency Hemodialysis: A Pilot Study

Abstract: Nine patients receiving maintenance high-efficiency hemodialysis were studied before and after a 12-week conditioning program to determine the efficacy of exercise immediately following hemodialysis. Each patient performed a combination of bicycle ergometry on the Schwinn Air-Dyne ergometer (SAE) and treadmill walking three times a week for a total exercise time of 15–35 min per session. A low-level Bruce treadmill test and an exercise test on the SAE were administered before and after training. Hematological,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…However, they reported that patients who persisted in the training program had better scores on the psycho logical tests. Finally, Ross et al [28] in a pilot study could not come to definite conclusions regarding the psychologi cal changes after applying a 12-week conditioning pro gram to a small group of HD patients, although some pos itive psychological trends were seen. Further studies need to determine whether and in what manner the psychoso cial and functional improvements brought about by exer cise training affect the HD patients' ability to work and their overall employment status.…”
Section: Resultsmentioning
confidence: 95%
“…However, they reported that patients who persisted in the training program had better scores on the psycho logical tests. Finally, Ross et al [28] in a pilot study could not come to definite conclusions regarding the psychologi cal changes after applying a 12-week conditioning pro gram to a small group of HD patients, although some pos itive psychological trends were seen. Further studies need to determine whether and in what manner the psychoso cial and functional improvements brought about by exer cise training affect the HD patients' ability to work and their overall employment status.…”
Section: Resultsmentioning
confidence: 95%
“…Hypertension is seen in the majority of patients and is considered one of the most important risk factors for cardiac and vascular diseases. Some trials have studied the effects of physical exercise on hypertension in HD patients, but have conflicting results [5, 17, 18, 19, 20]. In a recent non-randomized but controlled study, exercise during dialysis reduced the use of antihypertensive medications [21].…”
Section: Discussionmentioning
confidence: 99%
“…Although the intensity and the duration of exercise in the studies varies, all have included initial moderate aerobic training progressing to vigorous training for 30 min or more three times per week for Ն8 wk up to 12 mo (most studies 3 to 6 mo). On average, aerobic exercise training for 8 wk to 6 mo improves VO 2peak by approximately 17% (Figure 3), but there is considerable variability from study to study, and many studies have been uncontrolled (16,18,30,(32)(33)(34)(35)(36)41,43). Only two of these studies included patients who were on peritoneal dialysis (35,40).…”
Section: Aerobic Exercise Trainingmentioning
confidence: 99%
“…These other outcomes have included anemia, lipid levels, BP control, endothelial function, inflammation, mental health, and health-related quality of life. Although a few small studies have reported an improvement in anemia with vigorous aerobic exercise training (30,31), the majority of studies have not reported this benefit (32)(33)(34)36). Studies of the lipid effects of vigorous aerobic exercise training have also been mixed, with some showing a decrease in triglyceride (30,31) or an increase in HDL cholesterol (30,31) and others not showing any changes (34 -36).…”
Section: Aerobic Exercise Trainingmentioning
confidence: 99%